2021
DOI: 10.55365/1923.x2021.19.04
|View full text |Cite
|
Sign up to set email alerts
|

Why do People Refuse Entrepreneurship and How to Improve Entrepreneurial Education?

Abstract: The purpose of this paper is to measure entrepreneurial intentions with a clear timeframe for the intended behavior, thus going beyond a simple measure of attitude. It then looks at those who refuse the idea of becoming entrepreneurs to understand why This is something the literature on entrepreneurship has ignored so far. Samples were collected in 2018 from final year university students in Portugal. Data shows that trusting one’s own skills, valuing own job creation, valuing being one’s own boss and valuin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The basis of success in the development of the creative environment of the company is its management system, represented by a set of factors, among which it is necessary to distinguish the corporate culture and the culture of the organisation of activities. It is precisely the company's management system that creates an environment that unleashes or constrains the creative potential of the company's employees, which in turn constitutes the primary source of innovative solutions that can substantially change the organisation's activities (Gaspar and Mota, 2021). Therefore, the culture of innovation is of particular importance in understanding the role of creative potential in the project management process for the implementation of the company's strategy.…”
Section: Resultsmentioning
confidence: 99%
“…The basis of success in the development of the creative environment of the company is its management system, represented by a set of factors, among which it is necessary to distinguish the corporate culture and the culture of the organisation of activities. It is precisely the company's management system that creates an environment that unleashes or constrains the creative potential of the company's employees, which in turn constitutes the primary source of innovative solutions that can substantially change the organisation's activities (Gaspar and Mota, 2021). Therefore, the culture of innovation is of particular importance in understanding the role of creative potential in the project management process for the implementation of the company's strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on ESE have demonstrated that it can predict people's intentions to launch business because it reflects their level of self-belief. Many researches support that self-efficacy can strengthen entrepreneurial intention in conjunction with entrepreneurial education (Gaspar and Mota, 2021;Barakat et al, 2014). However, according to Graevenitz et al (2010), students' self-efficacy are susceptible to the signals which get from entrepreneurship courses.…”
Section: Entrepreneurial Self-efficacy (Ese)mentioning
confidence: 99%